Pengaruh Himbauan Pesan Tentang Lingkungan Hidup terhadap Perubahan Sikap Siswa SD - Fuady, Ikhsan; Yusnita, Titien; limilia, Putri (Jurnal Artikula, 2019)
Excessive production of waste that can destabilize ecosystems and environmental degradation. The impact on the ecosystem is a threat to public health so that the necessary environmental education outreach to the community. One strategy that can be done to maintain the quality of the environment is to provide environmental education from an early age to children who are still in elementary school. The role of the school community in school activities towards healthy environment in order to avoid negative environmental impacts. In addition, children can be an important influence on the behavior of parents and the people around them where environmental awareness and proper understanding must be rooted in the educational system at all levels of school education. The purpose of this research is to improve elementary students caring attitude towards the environment, especially the attitude of care for the litter.This research apply in Quasy Experimental method with Pretest Posttest Control Group Design. The results of this experimental study shows that the extension using call rational appeal (HR) of concern for the environment tends to be low (65%) while using the extension calls emotional appeal (HE) on the environment tends to be high (58%) to change the attitude of elementary school students. The conclusion of this study is the extension of environmental education at elementary students have a significant impact attitude change when using the emotional appeal.